MANAJEMEN RESIKO DAN STRATEGI RESILIENSI BANK LEHMAN BROTHERS (1850-2000) - Kharisma, Fresha; Purnomo, Marcello; Putra, Bagaskara Rahadi; Salsabila, Carissa Oktiara; Nabilah, Salma (Universitas Negeri Surabaya, 2022)
Lehman Bank is one of the largest banks in America that went bankrupt. This study aims to analyze the causes of the bankruptcy of Lehman Brother Bank, to perform external and internal analysis and analyze the SWOT and PESTEL strategies for the Lehman Brother company. This research method is to analyze SWOT and PESTEL using qualitative research. information or data from search results on the internet or from literature studies. The results of this study indicate that an analysis using SWOT and PESTEL has been carried out and has an impact on Lehman Brother, but Lehman Brother is still not advanced enough to advance technology, so Lehman Brother went bankrupt. Keyword: Lehman Brother bankruptcy; swot; pestel